A clinical case report on the treatment of small cell carcinoma of the esophagus at Hanoi Medical University Hospital - Hung, Nguyen Van; Chi, Do Huyen; Tu, Doan Trong; Manh, Pham Duy; Dinh, Lai Thi; Thuyen, Pham Dang (Tạp chí Nghiên cứu Y học, 2026)
Small cell neuroendocrine carcinoma of the esophagus (SCNEC) is a rare and highly aggressive histological subtype that requires a multimodal treatment approach, including chemotherapy, surgery, and radiotherapy. Among these options, concurrent chemoradiotherapy with etoposide and cisplatin (EP) regimen is an effective treatment choice for patients with locoregional disease. We report the case of a 61-year-old male patient diagnosed with stage cT4bN2M0 SCNEC who received radiotherapy combined with EP chemotherapy. Following treatment, endoscopic evaluation revealed marked tumor regression, leaving only a residual ulcer scar, and tumor markers returned to normal levels, indicating a complete clinical response (CCR). To date, follow-up has shown no evidence of local recurrence or distant metastasis, with a progression-free survival (PFS) of 24 months. This case demonstrates the efficacy and safety of combined radiotherapy and EP chemotherapy in locoregional SCNEC, highlighting its potential to achieve CCR and prolong PFS.